Quantitative susceptibility mapping (QSM) of white matter multiple sclerosis lesions: Interpreting positive susceptibility and the presence of iron. Issue 2 (18th August 2014) - Wisnieff, Cynthia; Ramanan, Sriram; Olesik, John; Gauthier, Susan; Wang, Yi; Pitt, David
<x xml:space="preserve">Abstract</x> Purpose Within multiple sclerosis (MS) lesions iron is present in chronically activated microglia. Thus, iron detection with MRI might provide a biomarker for chronic inflammation within lesions. Here, we examine contributions of iron and myelin to magnetic susceptibility of lesions on quantitative susceptibility mapping (QSM). Methods Fixed MS brain tissue was assessed with MRI including gradient echo data, which was processed to generate field (phase), R2* and QSM. Five lesions were sectioned and evaluated by immunohistochemistry for presence of myelin, iron and microglia/macrophages. Two of the lesions had an elemental analysis for iron concentration mapping, and their phospholipid content was estimated from the difference in the iron and QSM data. Results Three of the five lesions had substantial iron deposition that was associated with microglia and positive susceptibility values. For the two lesions with elemental analysis, the QSM derived phospholipid content maps were consistent with myelin labeled histology. Conclusion Positive susceptibility values with respect to water indicate the presence of iron in MS lesions, although both demyelination and iron deposition contribute to QSM. Magn Reson Med 74:564–570, 2015. © 2014 Wiley Periodicals, Inc.